1991
DOI: 10.1111/j.1600-0722.1991.tb01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Saliva composition and caries development in asthmatic patients treated with β2‐adrenoceptor agonists: a 4‐year follow‐up study

Abstract: – In an earlier study, we found that chronic treatment with β2‐adrenoceptor agonists in asthmatic subjects gave an impaired saliva secretion and a higher caries prevalence than in healthy controls. Twenty‐one of the asthmatics and their matched controls were examined 4 yr later in a follow‐up study. Samples of whole saliva stimulated by chewing and parotid saliva stimulated by citric acid were collected and dental caries was scored. In the asthmatic group the secretory rates of stimulated whole and parotid sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
3
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 19 publications
9
103
3
7
Order By: Relevance
“…However, only 42.4% of the asthma subjects used anti-asthma medications, indicating that the medication rather than the condition may play a role. Consistent with this hypothesis, a longitudinal study by Ryberg et al, [33] reported that chronic treatment with beta2-adrenoceptor agonists in asthmatics caused a decrease in salivary flow and an increase in caries incidence. Thomson et al, [24] also found a statistically significant increase in coronal caries among anti-asthma medication users.…”
Section: Introductionsupporting
confidence: 59%
“…However, only 42.4% of the asthma subjects used anti-asthma medications, indicating that the medication rather than the condition may play a role. Consistent with this hypothesis, a longitudinal study by Ryberg et al, [33] reported that chronic treatment with beta2-adrenoceptor agonists in asthmatics caused a decrease in salivary flow and an increase in caries incidence. Thomson et al, [24] also found a statistically significant increase in coronal caries among anti-asthma medication users.…”
Section: Introductionsupporting
confidence: 59%
“…Published studies on oral health in adults with asthma are relatively few and present large variations in ages of the participants, asthma severity, duration, medication and sample size [10,11,[22][23][24]. One explanation for this may be the difficulty involved in recruiting well-controlled, homogeneous groups with long-term disease.…”
Section: Discussionmentioning
confidence: 97%
“…Eloot et al [17] found that neither the length of the disease period in 3 to17-year-old children with asthma nor the medication or the severity of the asthma disease had a significant effect on the risk of developing caries or gingivitis. In studies by Ryberg et al [12,13], however, it was shown that asthmatic children who medicated with β 2 agonists had a decreased saliva secretion rate and increased levels of lactobacilli and mutans streptococci, in addition to more caries lesions, compared with healthy children. Mc Derra et al [8] found that 4-to 10-year-old children with asthma had more plaque, gingivitis and calculus compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported a correlation between childhood asthma and dental caries in pre-school children [6][7][8][9][10][11][12][13], while others have found no such connection [14][15][16]. Eloot et al [17] found that neither the length of the disease period in 3 to17-year-old children with asthma nor the medication or the severity of the asthma disease had a significant effect on the risk of developing caries or gingivitis.…”
Section: Introductionmentioning
confidence: 99%